Why gender matters in One Health - Mutua, Florence K. (International Livestock Research Institute, 2021)
Florence Mutua, epidemiologist at ILRI, discusses the role of gender in One Health and the actions that are need to strengthen gender in One Health. This film is part of the ILRI and CGIAR 'Investing in One Health' video series.